2017
DOI: 10.1021/acs.cgd.7b01224
|View full text |Cite
|
Sign up to set email alerts
|

Confined Crystallization of Organic Materials in Nanopipettes: Tracking the Early Stages of Crystal Growth and Making Seeds for Unusual Polymorphs

Abstract: Confined crystallization of organic materials in nanopipettes : tracking the early stages of crystal growth and making seeds for unusual polymorphs. Crystal Growth & Design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…In this framework, electrical devices allow ultrafast time response (down to nanoseconds), making them very attractive for monitoring of the dynamics of complex ensemble processes. Only very few attempts have been previously attempted, ranging from the use of nanopipette electrodes for tracking crystallization events in confinement, 13 to nanopore electrodes for DNA sequencing. 14 Very recently, a graphene field effect transistor (FET) was used to monitor in real-time the dynamics of self-assembly of molecules on a surface, 15 demonstrating that electrical readout can indeed be applied for monitoring processes of a large ensemble of interacting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, electrical devices allow ultrafast time response (down to nanoseconds), making them very attractive for monitoring of the dynamics of complex ensemble processes. Only very few attempts have been previously attempted, ranging from the use of nanopipette electrodes for tracking crystallization events in confinement, 13 to nanopore electrodes for DNA sequencing. 14 Very recently, a graphene field effect transistor (FET) was used to monitor in real-time the dynamics of self-assembly of molecules on a surface, 15 demonstrating that electrical readout can indeed be applied for monitoring processes of a large ensemble of interacting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and his colleagues , demonstrated that although the melt crystals of the d -mannitol and d -sorbitol seeds have thermodynamic stability, a different crystal can be formed by scattering the metastable seeds. Similarly, seeding failed to produce the desired polymorphic outcome because cross-nucleation occurred for other crystallization systems. , …”
Section: Progress and Problems In Seeding Techniquesmentioning
confidence: 99%
“…11,17,29 The use of nanopores, however, allows for convenient analysis of precipitation at the nanoscale by using an applied potential to mix solutions inside a confined volume and monitor the resulting changes in the ion current. Previously, the precipitation of weakly soluble phosphate salts of Zn, 30 Ca, 31 Co, 31 as well as CoCl 2 , 32 and even organic crystals 33 have been studied. We have used this approach to measure induction times for ACC precipitation in the presence of various scale inhibitors.…”
Section: Introductionmentioning
confidence: 99%